2014
DOI: 10.3892/etm.2014.2018
|View full text |Cite
|
Sign up to set email alerts
|

Levels of acylation stimulating protein and the complement component 3 precursor are associated with the occurrence and development of coronary heart disease

Abstract: The aim of the present study was to investigate whether acylation stimulating protein (ASP) and complement component 3 (C3) are associated with the occurrence and development of coronary heart disease (CHD). The participants of the study were divided into three groups, including the healthy control (n=42), metabolic syndrome (MS, n=56) and CHD (n=62) groups. An enzyme-linked immunosorbent assay was used to measure the ASP concentrations, while an immunoturbidimetric assay was employed to determine the C3 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Bratti et al revealed that the C3 level was positively correlated with body mass index and significantly decreased with weight loss after bariatric surgery. Jiang et al found that in CAD patients, serum C3 was significantly higher than in controls, and was positively associated with the severity of CAD [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Bratti et al revealed that the C3 level was positively correlated with body mass index and significantly decreased with weight loss after bariatric surgery. Jiang et al found that in CAD patients, serum C3 was significantly higher than in controls, and was positively associated with the severity of CAD [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…[30] Furthermore, ASP levels were positively correlated with cTnI in patients with acute MI regardless of statins therapy, since ASP levels are positively correlated with severity of CAD and cTnI indicating that ASP is implicated in pathogenesis of CAD due to metabolic alterations in lipid profile. [31] There are numerous limitations of the current study, relative small sample size, determination of ASP receptors in coronary vessels, and HMG-CoA activity in response to the ASP levels are the main points that limit the present study. On the other hand, this study may be to our knowledge, the first novel study regarding the effect of statins on ASP levels in CAD.…”
Section: Discussionmentioning
confidence: 88%
“…The protein and mRNA expression levels of complement C3 were found to be associated with the occurrence and development of coronary heart disease [ 36 ], higher C3 was significantly associated with presence and greater extent of arterial calcification, and C3 could be a potential non-invasive biomarker of early diagnosis of atherosclerosis [ 37 ]. Activation of the immune response by elevating hydroperoxides levels, further activating NF-kB signaling, may be a key aging feature in the mouse heart [ 38 ]. In addition, Lian et al reported that astroglial NF-kB/C3 activation led to impaired synaptic density and dendritic morphology in brain tissue of Alzheimer’s disease (AD) patients [ 39 ], and the expressions of C3, C4 and C5 mRNA increased with age in C57BL/6 mice brain [ 37 - 39 ].…”
Section: Discussionmentioning
confidence: 99%